Low compressive potency DS-dune sand utilizing PW-plastic waste for the construction of roads. (2021) - Singh Parihar, Hemant; Verma, Mohit
Abstract: In India, western part is mostly deserted which have mostly dune sand. According to Indian Standard Classification System, dune sand has nil plasticity characteristics and nil cohesion. Dune sand has less compressive-strength. Hence, by the stabilization of DS, we can use it for various constructions like highways, helipad and airfield constructions. We can use plastic waste like polybags as admixture to stabilize the dune sand. This manuscript presents the simulation outcomes on dune sand mixed with polybags. This is also a way to reuse of PW with reinforcing the DS. It will help in plastic waste removal and management. The size of polybag waste utilized is 5 mm × 5 mm. Different proportions 0%, 0.05%, 0.06%, 0.7%, %, 0.9% and 1.0% of polybag waste and different dry densities 1.66 (M.D.D.), 1.62 & 1.57 gm/cc of DS were mixed and used for testing. The test of particle magnitude dissemination, test on benchmark proctor, variable permeability is carried to attain results.